PENGEMBANGAN KYORUGI SCORING DISPLAY SYSTEM DENGAN ARDUINO UNO DAN BORLAND DELPHI 7 - Dila Umnia Soraya; Basalim Jabar (LPPM Universitas Cipta Mandiri, 2017)
This research aims to describe the Kyorugi Scoring Display development procedure System using Borland Delphi 7 and Arduino UNO as remote control. Development Kyorugi Scoring Display System is one solution to problems for board supply companies Taekwondo match scores (scoreboard) to increase the effectiveness of filling in match scores computer interface based. Because there are still many physical match scoreboards weakness, namely that it takes a long time to set the score because it uses manual push button which has an impact on match schedule delays, the display of the Taekwondo match scoreboard also incomplete, the scoreboard remote control is too big, making it difficult for the judges to judge, and The dimensions of the scoreboard are too large, making it difficult to arrange the instrumentation match. Based on these problems, it is necessary to develop an interface-based scoreboard with attractive features and displays that make it easier for judges to monitor scores, especially on taekwondo competition. Kyorugi Scoring Display System is a computer interface (software). developed using the Borland Delphi 7 application, and Ardunino UNO as a remote control. Product testing is carried out by testing the product with several experts and covers every layer product. Product testing results show that the Kyorugi Scoring Display System runs well proven by the correspondence between the input from the remote control and the display on the application. So, it can be concluded that the Kyorugi Scoring Display System can be a solution to the problem In filling in scores for Taekwondo matches, we use a physical scoreboard that has many lack.